2008
DOI: 10.1016/j.ejcts.2008.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Ascending aortic cannulation in acute aortic dissection type A: the Hannover experience☆☆☆

Abstract: Direct cannulation of the ascending aorta is an easy and safe method in patients with AADA. This technique, which also avoids retrograde flow in the downstream aorta, is an alternative to time-consuming axillary artery access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(69 citation statements)
references
References 25 publications
2
60
0
7
Order By: Relevance
“…Our early outcomes in the TAA group, 4.3% mortality and 11% stroke, are acceptable compared with other reports not only about FA cannulation, 25) and ascending cannulation, [15][16][17][18] but also with axillary cannulation, [8][9][10] in the treatment of AAAD. As described above, there are advantages and disadvantages to each cannulation technique.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Our early outcomes in the TAA group, 4.3% mortality and 11% stroke, are acceptable compared with other reports not only about FA cannulation, 25) and ascending cannulation, [15][16][17][18] but also with axillary cannulation, [8][9][10] in the treatment of AAAD. As described above, there are advantages and disadvantages to each cannulation technique.…”
Section: Discussionsupporting
confidence: 63%
“…13,14) Recently, direct cannulation into the dissected ascending aorta has been reported by several surgeons. [15][16][17][18] This technique can be performed rapidly without injury to the peripheral arteries, but there are concerns that it may increase the risks of rupture, extension of the dissection and malperfusion. TAA cannulation is an old technique that was initially described in the early 1970s.…”
Section: Discussionmentioning
confidence: 99%
“…It provides an advantage of antegrade perfusion but has the risk of the false lumen cannulation, which might lead to aortic rupture, or malperfusion [11]. This cannulation technique includes direct cannulation of the dissected ascending aorta [12][13][14] or transapical cannulation of the ascending aorta [10]. This technique is not recommended as the first cannulation option.…”
Section: In This Issue Of the European Research Journalmentioning
confidence: 99%
“…They cannulated the ascending aorta at the site of the minimal distances of the dissected layers and used double purse-string sutures for cannula fixation. They showed that this technique is a safe option with malperfusion in 3 (2.5%) patients, aortic rupture in 1 (0.8%) patient, and hospital mortality in 18 (15%) patients [13].…”
Section: In This Issue Of the European Research Journalmentioning
confidence: 99%
See 1 more Smart Citation